Curricular Policies for Early Childhood Education: Global Influences and Local Translations in Brazil and Portugal - Peixer, Daniela Neto Oliveira; Nazário, Roseli (Revista Diálogo Educacional, 2025)
This study analyzes the influence of international organizations on Early Childhood Education curriculum policies in Brazil and Portugal, investigating how global guidelines are interpreted and recontextualized in the construction of national curricula. The research adopts a qualitative approach, bibliographic in nature and articulated with documentary analysis of the national curriculum policies of both countries — the National Common Curricular Base (BNCC) and the Curricular Guidelines for Preschool Education (OCEPE) — grounded in Ball's Policy Cycle (2011, 2022), and attentive to the historical, political, and economic specificities of each context. The results reveal that, although they share converging historical trajectories, Brazil and Portugal differ in their degree of autonomy in the elaboration of educational policies. A growing articulation between curriculum policies and international guidelines is observed, with emphasis on skills development, curriculum standardization, and alignment with global market demands. The study contributes to the debate on educational policy formulation by highlighting the contradictions of the BNCC, the persistent fragmentation of Early Childhood Education, and the need to strengthen democratic and culturally situated perspectives capable of resisting the homogenizing pressures of global capitalism.